Solution adsorption formation of a π-conjugated polymer/graphene composite for high-performance field-effect transistors - Liu, Yun (2019)
Semiconducting polymers with π‐conjugated electronic structures have potential application in the large‐scale printable fabrication of high‐performance electronic and optoelectronic devices. However, owing to their poor environmental stability and high‐cost synthesis, polymer semiconductors possess limited device implementation. Here, an approach for constructing a π‐conjugated polymer/graphene composite material to circumvent these limitations is provided, and then this material is patterned into 1D arrays. Driven by the π–π interaction, several‐layer polymers can be adsorbed onto the graphene planes. The low consumption of the high‐cost semiconductor polymers and the mass production of graphene contribute to the low‐cost fabrication of the π‐conjugated polymer/graphene composite materials. Based on the π‐conjugated system, a reduced π–π stacking distance between graphene and the polymer can be achieved, yielding enhanced charge‐transport properties. Owing to the incorporation of graphene, the composite material shows improved thermal stability. More generally, it is believed that the construction of the π‐conjugated composite shows clear possibility of integrating organic molecules and 2D materials into microstructure arrays for property‐by‐design fabrication of functional devices with large area, low cost, and high efficiency.